Efficacy of early rituximab treatment in primary Sjögren’s syndrome: a systematic review and meta-analysis - Mohammad Shahdadian; Mohammad Ali Saghiri; Eugenio Capitle (Journal of Rheumatic Diseases)
Objective: This systematic review and meta-analysis aimed to assess Rituximab (RTX)’s efficacy and safety in primary Sjögren’s syndrome (pSS), particularly how treatment timing influences outcomes.Methods : : The study included randomized controlled trials (RCTs) and quasi-experimental studies evaluating RTX in pSS patients, focusing on disease activity (European League Against Rheumatism Sjögren’s Syndrome Disease Activity Index [ESSDAI] score) and adverse events (AEs). Searches were conducted in MEDLINE, Embase, SCOPUS, and Cochrane Library databases up to July 2024. Risk of bias was assessed using Cochrane Risk of Bias 2.0 (RoB 2) and Joanna Briggs Institute (JBI) checklists. Metaanalysis was performed in Stata 17 with a random-effects model, reporting mean differences in ESSDAI and I² for heterogeneity.Results : : From 555 articles, 15 studies were included (4 RCTs and 11 quasi-experimental studies). RCT meta-analysis showed a mean difference of 0.09 (95% confidence interval [CI]: –0.43, 0.61), indicating no significant RTX efficacy. In contrast, the pooled quasi-experimental analysis revealed a mean difference of –4.36 (95% CI: –5.83, –2.89), suggesting a significant reduction in disease activity. Meta-regression indicated no significant correlation between RTX efficacy and mean disease duration. Subgroup analysis of disease duration (under vs. over 60 months) showed no significant difference. Safety assessment indicated no significant differences in AEs between RTX and placebo in RCTs. In quasi-experimental studies, infusion reactions and infections were the most common AEs, with serious infections being the most severe.Conclusion : : RTX did not show significant improvement in RCTs. However, RTX significantly reduced pSS activity at week 24 or month 6 following treatment, based on quasi-experimental studies. We found no significant correlation between RTX efficacy and disease duration.